Immunomodulatory effect of first-in-human PeriCord cardiac bioimplant: preliminary data of the PERISCOPE clinical trial. (3rd October 2022) - Monguio-Tortajada, M; Prat-Vidal, C; Gastelurrutia, P; Camara-Rosell, M L; Cediel, G; Teis, A; Revuelta-Lopez, E; Roura, S; Galvez-Monton, C; Lupon, J; Vilarrodona, A; Munoz-Guijosa, C; et al.
Abstract: Background: The PERISCOPE is a first-in-human, phase I, double blind, one centre clinical trial to test the safety of the PeriCord, an advanced therapy medicinal product (PEI18–140), for the treatment of patients with infarcted myocardial tissue. The PeriCord is a GMP-complying allogeneic engineered tissue graft consisting on a decellularised pericardial matrix colonised with umbilical cord Wharton's jelly mesenchymal stromal cells. The PeriCord implantation has shown to promote damaged tissue revascularisation, reduce infarct size, adverse remodelling and fibrosis, and ultimately improve cardiac function preclinically. Purpose: To assess the safety and monitor the monocyte and cytokine response after PeriCord implantation in patients with infarcted myocardial tissue. Methods: The PERISCOPE clinical trial has been approved by AEMPS and the Local Ethics Committee of our institution (Eudra-CT 2018–001964–49). Twelve patients with transmural myocardial infarction (>50% by MRI) who were candidates for surgical revascularisation were included: two roll-in and 10 randomised into a Control group (n=5; CABG) or Treatment group (n=5; n=7 in total; CABG and PeriCord implantation over the transmural myocardial scar). In conjunction with clinical follow-up, whole blood was sampled at baseline and 3-, 6-, and 9-days post-surgery for monocyte populations analysis by flow cytometry and plasma cytokine and monocyte chemoattractant chemokine levels by multiplex ELISA. Results: The target patient enrolment has been met and no adverse effects related to PeriCord implantation were observed so far. Recruitment of CCR2+ activated monocytes in peripheral blood peaked on day 3 post-surgery in both groups (increase in the %CCR2+ monocytes of 6.1±5.7% in Control, p=0.38; and 6.5±1.8% in PeriCord Treated patients, p=0.0004), concomitant with a surge in the monocyte chemoattractant CCL2 plasma levels. At the same time, there was a decrease in the number of "non-classical" monocytes regardless of treatment (decrease in CD14-/CD16+ monocytes of 16.7±11.1% in Control, p<0.01; and 24.0±15.0% in PeriCord Treated patients, p<0.001) and a marked reduction in CX3CR1 expression in monocytes of PeriCord treated patients (decrease of 53.2±20.6% in mean fluorescence intensity at day 3, p<0.01), while plasma CX3CL1 levels were undetectable. Both populations recovered on day 9 only in treated patients (p<0.05). Conclusions: Implantation of the PeriCord in myocardial infarction patients did not promote adverse reactions and modulated circulating monocyte subsets that have been associated with post-infarction myocardial tissue healing (CCR2 and CX3CR1). These results will be analysed for correlation with therapeutic benefits by the end of patient follow-up. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto Carlos III, Generalitat de Catalunya